Long COVID: An approach to clinical assessment and management in primary care - Rubeshan Perumal; Letitia Shunmugam; Kogieleum Naidoo (South African Family Practice)
Long COVID is an emerging public health threat, following swiftly behind the surges of acute infection over the course of the COVID-19 pandemic. It is estimated that there are already approximately 100 million people suffering from Long COVID globally, 0.5 million of whom are South African, and for whom our incomplete understanding of the condition has forestalled appropriate diagnosis and clinical care. There are several leading postulates for the complex, multi-mechanistic pathogenesis of Long COVID. Patients with Long COVID may present with a diversity of clinical phenotypes, often with significant overlap, which may exhibit temporal heterogeneity and evolution. Post-acute care follow-up, targeted screening, diagnosis, a broad initial assessment and more directed subsequent assessments are necessary at the primary care level. Symptomatic treatment, self-management and rehabilitation are the mainstays of clinical care for Long COVID. However, evidence-based pharmacological interventions for the prevention and treatment of Long COVID are beginning to emerge. This article presents a rational approach for assessing and managing patients with Long COVID in the primary care setting.